Policy instruments for environmental and natural resource management - Sterner, Thomas 1952-; Coria, Jessica (New York, N.Y. RFF Press, 2012)
"Thomas Sterner's book is an attempt to encourage more widespread and careful use of economic policy instruments. The book compares the accumulated experiences of the use of economic policy instruments in the U.S. and Europe, as well as in rich and poor countries in Asia, Africa, and Latin America. Ambitious in scope, it discusses the design of instruments that can be employed in any country in a wide range of contexts, including transportation, industrial pollution, water pricing, waste, fisheries, forests, and agriculture."--Provided by publisher.
Includes bibliographical references and index.
Keywords: Environmental policy; Conservation of natural resources -- Government policy